Health orientation and individual tendencies of a sample of Italian genetic testing consumers - Serena Oliveri; Ilaria Durosini; Ilaria Cutica; Clizia Cincidda; Francesca Spinella; Marina Baldi; Alessandra Gorini; Gabriella Pravettoni (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Over the last decade, genetic testing (GT) had markedly spread in European countries and struggled the debate concerning the psychological effects on the population. The aim of this study was to investigate the individual tendencies of GT consumers in a sample of Italian citizens. Methods A total of 152 Italian clients from GenomaLab, a private genetic company, were enrolled from February 2016 to September 2018 and completed an ad hoc survey. Results Results showed that GT consumers were motivated to preserve their well‐being, they felt responsible for their health, they were neither pessimistic nor optimistic toward negative occurrences, and poorly inclined to take high risks in their lives. Participants who had suffered from a disease in the past appear to be less tolerant to the uncertainty for future negative events. Conclusion Our results depict Italian GT consumers as health‐oriented, focused on prevention, who do not have a pessimistic perception of their condition but do not like to “bet” on their health, and probably their intention (and belief) is to acquire genetic information in order to reduce uncertainty and increase their decision‐making “power” related to their health. Taken together, all these results contribute to describe the population of GT users in European countries, to regulate the provision of GT results and to entail the communication of genetic risk information based on a consumers’ personal profile.